2013
DOI: 10.1186/1471-2202-14-50
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of two novel odorant receptors in the locust (Locusta migratoria)

Abstract: BackgroundOlfaction in animals is important for host localization, mating and reproduction in heterogeneous chemical environments. Studying the molecular basis of olfactory receptor neurons (ORNs) systems can elucidate the evolution of olfaction and associated behaviours. Odorant receptors (ORs) in insects have been identified, particularly in the holometabolous model Drosophila, and some of them have been functionally studied. However, ORs in the locust—a hemimetabolous model insect and the most important ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…Previous PCR experiment results showed that LmigOR3 was specifically expressed in the antennae of locust from nymph to adult at high levels (Xu et al, 2013). To localize LmigOR3 expression to a type of sensillum, we performed in situ hybridization experiments with DIG-labeled LmigOR3 sense and antisense probes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous PCR experiment results showed that LmigOR3 was specifically expressed in the antennae of locust from nymph to adult at high levels (Xu et al, 2013). To localize LmigOR3 expression to a type of sensillum, we performed in situ hybridization experiments with DIG-labeled LmigOR3 sense and antisense probes.…”
Section: Resultsmentioning
confidence: 99%
“…Adult locusts ( L. migratoria ) in this study were obtained and raised as previously described (Xu et al, 2013). Intact antennae were dissected using forceps and stored at −80°C until further processing for in situ hybridization or to recover mRNA.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations